Amphetamine, but not methylphenidate, increases ethanol intake in adolescent male, but not in female, rats. Issue 4 (19th February 2018) - Ruiz, Paul; Calliari, Aldo; Genovese, Patricia; Scorza, Cecilia; Pautassi, Ricardo Marcos
Abstract: Introduction: There has been an increasing interest in analyzing the interactions between stimulants and ethanol during childhood and adolescence. Stimulants are used to treat attention‐deficit hyperactivity disorder (ADHD) in these developmental stages, during which ethanol initiation and escalation often occur. Methods: This study assessed the effects of repeated d‐amphetamine (AMPH) or methylphenidate (MPH) treatment during adolescence [male and female Wistar rats, between postnatal day (PD) 28 to PD34, approximately] on the initiation of ethanol intake during a later section of adolescence (PD35 to PD40). Results: Amphetamine and MPH exerted reliable acute motor stimulant effects, but there was no indication of sensitized motor or anxiety responses. MPH did not affect dopamine (DA) levels, whereas AMPH significantly reduced insular levels of DA in both sexes and norepinephrine levels in females only. Repeated treatment with AMPH, but not with MPH, enhanced ethanol intake during late adolescence in male, but not in female, rats. Conclusion: A short treatment with AMPH during adolescence significantly altered DA levels in the insula, both in male and females, and significantly enhanced ethanol intake in males. The present results suggest that, in adolescent males, a very brief history of AMPH exposure can facilitate the initiation of ethanol intake. Abstract : This study assessed the effects of repeated d‐amphetamine (AMPH) or methylphenidate (MPH) treatment during adolescence on the initiation of ethanol intake during a later section of adolescence. Repeated treatment with AMPH, but not with MPH, enhanced ethanol intake during late adolescence in male, but not in female, rats. The present results suggest that, in adolescent males, a very brief history of AMPH exposure can facilitate the initiation of ethanol intake.